2022
DOI: 10.1111/jam.15720
|View full text |Cite
|
Sign up to set email alerts
|

A SARS-CoV-2 oral vaccine development strategy based on the attenuated Salmonella type III secretion system

Abstract: Aims This study aimed to provide a safe, stable and efficient SARS‐CoV‐2 oral vaccine development strategy based on the type III secretion system of attenuated Salmonella and a reference for the development of a SARS‐CoV‐2 vaccine. Methods and Results The attenuated Salmonella mutant Δ htrA ‐VNP was used as a vector to secrete the antigen SARS‐CoV‐2 based on the type III secretion system (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The promoter sifB (pSifB) is a Salmonella -specific regulatory expression promoter that is initiated by the intracellular microenvironment, such as low pH and low phosphate. 33 , 34 Fluorescence images showed that the VNP-pSifB-RFP strain selectively expressed RFP after entering macrophages but not in regular media. VNP-pSifB-RFP specifically expressed RFP after entering macrophages, while the strain cultured in normal medium did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The promoter sifB (pSifB) is a Salmonella -specific regulatory expression promoter that is initiated by the intracellular microenvironment, such as low pH and low phosphate. 33 , 34 Fluorescence images showed that the VNP-pSifB-RFP strain selectively expressed RFP after entering macrophages but not in regular media. VNP-pSifB-RFP specifically expressed RFP after entering macrophages, while the strain cultured in normal medium did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The VNP strain constitutively expressing RFP (VNP-RFP strain), green fluorescent protein (GFP) (VNP-GFP strain), bioluminescence (LuxCDABE) (VNP-Lux strain), and the VNP strain controllably expressing RFP with the aid of the sifB promoter (VNP-psifB-RFP strain) were all constructed as described previously. 33 All plasmids used in this study were constructed using the ClonExpress Ultra One Step Cloning Kit V2 (Vazyme, C116, Nanjing, China). The constructed plasmids, including pJ23100-RFP, pJ23100-Lux, and psifB-RFP, were electrotransformed into VNP competent cells, with the transferred empty vector plasmids serving as blank control strains and denoted as VNP-NC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation